2019
DOI: 10.1631/jzus.b1900190
|View full text |Cite
|
Sign up to set email alerts
|

Integrated 3D bioprinting-based geometry-control strategy for fabricating corneal substitutes

Abstract: Background: The shortage of donor corneas is a severe global issue, and hence the development of corneal alternatives is imperative and urgent. Although attempts to produce artificial cornea substitutes by tissue engineering have made some positive progress, many problems remain that hamper their clinical application worldwide. For example, the curvature of tissue-engineered cornea substitutes cannot be designed to fit the bulbus oculi of patients. Objective: To overcome these limitations, in this paper, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 24 publications
1
41
0
1
Order By: Relevance
“…Given that corneal stromal bioprinting has shown encouraging results up to now, one can consider expanding this knowledge to manufacturing in vitro the remaining layers of the cornea, despite their distinct characteristics relative to the stroma. Two examples of studies that experimented with epithelial and endothelial corneal bioprinting are listed in Table 1 [90,91]. In the study by Zhang et al [90], human CEpCs were embedded in 15% GelMa hydrogels and printed by extrusion.…”
Section: Future Directions Of Corneal Bioprinting: Full-thickness Hummentioning
confidence: 99%
See 1 more Smart Citation
“…Given that corneal stromal bioprinting has shown encouraging results up to now, one can consider expanding this knowledge to manufacturing in vitro the remaining layers of the cornea, despite their distinct characteristics relative to the stroma. Two examples of studies that experimented with epithelial and endothelial corneal bioprinting are listed in Table 1 [90,91]. In the study by Zhang et al [90], human CEpCs were embedded in 15% GelMa hydrogels and printed by extrusion.…”
Section: Future Directions Of Corneal Bioprinting: Full-thickness Hummentioning
confidence: 99%
“…Two examples of studies that experimented with epithelial and endothelial corneal bioprinting are listed in Table 1 [90,91]. In the study by Zhang et al [90], human CEpCs were embedded in 15% GelMa hydrogels and printed by extrusion. In the other study by Kim et al [91], human CECs were embedded in a gelatin-RGD bioink and printed in an amniotic membrane support.…”
Section: Future Directions Of Corneal Bioprinting: Full-thickness Hummentioning
confidence: 99%
“…It acts as a mechanical and chemical barrier protecting the inner eye from external agents such as mechanical damage, microorganisms or ultraviolet radiation [29]. As a complex tissue, it is divided into five differentiated layers (Figure 3): epithelium, Bowman's membrane, stroma, Descement's membrane and endothelium [28,30]. The corneal epithelium is composed of a few layers of epithelial cells that form the outermost area of the cornea.…”
Section: Corneamentioning
confidence: 99%
“…[ 137 ] On these colloids, human corneal endothelial cells (ECs), bovine corneal keratinocytes, and rabbit corneal ECs can maintain a normal phenotype. [ 138 ] Collagen gel and PCL membranes have been used as cell carriers to reconstruct the cornea in animal in vivo models, but clinical trials and practical applications in humans have not been reported. [ 139 ]…”
Section: Application Of 3d Cell Culturementioning
confidence: 99%